Methods of Observing and Analyzing Students' Activity in Fine Arts Classes - Nadirxanova Nilufar (International Journal on Integrated Education, 2026)
In the following article the methods of monitoring and analyzing the activities of children in visual arts exercises are reconsidered from the viewpoint of visual fine arts. This article examines the methods of observing, monitoring, and analyzing students' activities in fine arts classes. Particular attention is given to the pedagogical principles, instructional techniques, and assessment criteria used in visual arts education. The study highlights the importance of exhibitions, excursions, vernissage lessons, thematic drawing, and creative projects in developing students’ artistic skills, imagination, aesthetic perception, and emotional responsiveness. Furthermore, the article discusses innovative approaches to evaluating students’ achievements in accordance with competency-based education principles and the requirements of the Bologna Process. The role of visual aids, digital technologies, inclusive educational practices, and alternative educational programs in improving the effectiveness of fine arts instruction is also analyzed. The findings indicate that systematic observation and comprehensive assessment contribute significantly to the development of creativity, critical thinking, visual literacy, and artistic competence among learners.